2021
DOI: 10.9770/jesi.2021.8.4(23)
|View full text |Cite
|
Sign up to set email alerts
|

Core features for the design of remuneration systems for sustainable human resource management during the Covid-19 pandemic: Polish companies’ experiences

Abstract: Fulfilling the objectives of sustainable development aimed at combining economic, social and ecological objectives is supported by the concept of Sustainable Human Resource Management (SHRM). SHRM practices enable the maintenance, renewal and restoration of human resources. The article fills a research gap on the characteristics of remuneration systems in SHRM. The purpose of this study is to reveal the remuneration practices that allow organisations to implement sustainable human resource management's charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…With teleworkers no longer physically present in the office, performance evaluation centered around productivity became crucial during the pandemic. Without proper oversight of productivity, variable compensation programs may yield unfair outcomes (Kawaguchi & Motegi, 2021;Kinowska, 2021;Silva & Moraes, 2021). These findings are corroborated by other studies, demonstrating that organizations and countries that failed to adequately compensate their workers experienced a loss of human capital (Alonge, 2021;Butterick & Charlwood, 2021;.…”
Section: The Pandemic's Effects On Hrmsupporting
confidence: 59%
See 1 more Smart Citation
“…With teleworkers no longer physically present in the office, performance evaluation centered around productivity became crucial during the pandemic. Without proper oversight of productivity, variable compensation programs may yield unfair outcomes (Kawaguchi & Motegi, 2021;Kinowska, 2021;Silva & Moraes, 2021). These findings are corroborated by other studies, demonstrating that organizations and countries that failed to adequately compensate their workers experienced a loss of human capital (Alonge, 2021;Butterick & Charlwood, 2021;.…”
Section: The Pandemic's Effects On Hrmsupporting
confidence: 59%
“…According to Liang et al (2022), sustainable human resource management (SHRM) played a crucial role in fostering a safe, mentally healthy, and productive environment during the pandemic. Kinowska (2021) and Azizi et al (2021) further demonstrated that this approach encompasses fair compensation, responsible leadership, collaboration, and effective communication, potentially extending into the post-pandemic era.…”
Section: The Pandemic's Effects On Hrmmentioning
confidence: 98%
“…Com os trabalhadores não mais presentes fisicamente no escritório, a avaliação de desempenho centrada na produtividade tornou-se crucial durante a pandemia. Sem uma supervisão adequada da produtividade, os programas de remuneração variável podem gerar resultados injustos (Kawaguchi & Motegi, 2021;Kinowska, 2021;Silva & Moraes, 2021). Esses achados são corroborados por outros estudos, demonstrando que organizações e países que não conseguiram remunerar adequadamente seus trabalhadores sofreram uma perda de capital humano (Alonge, 2021;Butterick & Charlwood, 2021;.…”
Section: Os Efeitos Da Pandemia Na Gpunclassified
“…De acordo com Liang et al (2022), durante a pandemia, a gestão sustentável de pessoas (GSP) desempenhou um papel crucial na promoção de um ambiente seguro, mentalmente saudável e produtivo. Kinowska (2021) e Azizi et al (2021) demonstraram ainda que essa abordagem abrange remuneração justa, liderança responsável, colaboração e comunicação eficaz, podendo se estender para o período pós-pandemia.…”
Section: Os Efeitos Da Pandemia Na Gpunclassified